A phase 1, open-label, randomized study to compare the immunogenicity and safety of different administration routes and doses of virosomal influenza vaccine in elderly. Issue 44 (17th October 2016) - Levin, Yotam; Kochba, Efrat; Shukarev, Georgi; Rusch, Sarah; Herrera-Taracena, Guillermo; van Damme, Pierre
Abstract: Background: Influenza remains a significant problem in elderly despite widespread vaccination coverage. This randomized, phase-I study in elderly compared different strategies of improving vaccine immunogenicity. Methods: A total of 370 healthy participants (⩾65 years) were randomized equally 1:1:1:1:1:1 to six influenza vaccine treatments (approximately 60–63 participants per treatment arm) at day 1 that consisted of three investigational virosomal vaccine formulations at doses of 7.5, 15, and 45 μg HA antigen/strain administered intradermally (ID) by MicronJet600™ microneedle device (NanoPass Technologies) or intramuscularly (IM), and three comparator registered seasonal vaccines; Inflexal V™ (Janssen) and MF59 adjuvanted Fluad™ (Novartis) administered IM and Intanza™ (Sanofi Pasteur) administered ID via Soluvia™ prefilled microinjection system (BD). Serological evaluations were performed at days 22 and 90 and safety followed-up for 6 months. Results: Intradermal delivery of virosomal vaccine using MicronJet600™ resulted in significantly higher immunogenicity than the equivalent dose of virosomal Inflexal V™ administered intramuscularly across most of the parameters and strains, as well as in some of the readouts and strains as compared with the 45 μg dose of virosomal vaccine formulation. Of 370 participants, 300 (81.1%) reported ⩾1 adverse event (AE); more participants reported solicited local AEs (72.2%) than solicited systemic AEs (12.2%). Conclusions: Intradermal delivery significantly improved influenza vaccine immunogenicity compared with intramuscular delivery. Triple dose (45 μg) virosomal vaccine did not demonstrate any benefit on vaccine's immunogenicity over 15 μg commercial presentation. All treatments were generally safe and well-tolerated.